Learning from unrealized versus realized prices - Kathleen Ngangoue; Georg Weizsäcker (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Our market experiment investigates the extent to which traders learn from the price, differentiating between situations where orders are submitted before versus after the price has realized. When market participants have to submit their bids conditional on the price, they show a bias by reacting only to their private information and not to the hypothetical value of the price. In a sequential trading mechanism, where the price is known at the bid submission, bids react to price to an extent that is roughly consistent with the benchmark theory.
Keywords: D82; D81; C91; 330; Naive Expectations; Asymmetric Information; Rational Expectations; Sequential Markets